Financial Performance with Asset Quality as Intervening Variable: Liquidity, Solvency and Operational Efficiency - Ningsih, Selfi Hastria; Risetadi, Aslan Hari; Gustika, Roza; Yeni, Fitri (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
Some banks in Indonesia that experience high solvency reflect an expansion strategy and aggressive lending. However, it also shows that there is a great risk in this large lending. Furthermore, the decline in asset quality has led to a disruption in financial stability due to an increase in operating expenses and a surge in impairment of financial assets. The purpose of this paper is to determine the effect of Liquidity, Solvency and Operational Efficiency on financial performance with Asset Quality as an intervening variable in Conventional Commercial Banks in Indonesia. The analysis was conducted based on a panel data approach of 32 commercial banks listed on the Indonesian stock exchange during 2019-2023. The results showed that liquidity and operational efficiency affect asset quality while solvency does not. Then the variables of liquidity, solvency, operational efficiency and asset quality partially influence bank performance. Then other findings show that asset quality can mediate the relationship between liquidity and solvency on bank performance. This shows that both directly and with the presence of asset quality as an intervening variable liquidity and solvency and operational efficiency have a positive influence on banking performance.